KAJIAN MOLEKULER LUMBA-LUMBA HIDUNG BOTOL (Tursiops sp.) ASAL LAUT JAWA BERDASAR URUTAN GEN CYTOCHROME C OXIDASE SUB-UNIT II (COX II) (Molecular Studies of Bottlenose Dolphins (Tursiops sp.) from Java Sea by Gene Sequences of Cytochrome C Oxidase Sub-Unit II (COX II)) - Rini Widayanti; Yuda Heru Fibrianto (Universitas Syiah Kuala, 2016)
The purpose of this study was to examine the molecular basis of Tursiops sp. originated from Java sea based on gene sequences ofCytochrome C Oxidase sub-unit II. Samples of blood were collected from five male bottlenose dolphins from PT. Wersut Seguni Indonesiacaptivity. Total deoxyribonucleic acid (DNA) was isolated from blood samples, then amplified by polymerase chain reaction (PCR), sequenced,and the data were analyzed using MEGA version 5.1 program. The amplification result of the PCR product obtained 824 base pairs (bp), andDNA sequencing obtained 684 nucleotides constituent of COX II genes that encode 228 amino acids making up the COX II. Nucleotide andamino acid sequence of COX II bottlenose dolphins originated from Java sea has a very high homology to Tursiops aduncus that are 99.13%and 100% respectively. Phylogram by neighbour joining method based on the nucleotide sequence of COX II gene indicating bottlenose dolphinsfrom Java sea belongs to group of Tursiops aduncus.Key words: bottlenose dolphin, COX II gene, nucleotide, Jawa Sea